Evaluating the resistance pattern of gram-negative bacteria during three years at the nephrology ward of a referral hospital in southwest of Iran - Iman Karimzadeh; Niloofar Sadeghimanesh; Mona Mirzaee; Mohammad Mahdi Sagheb (Society of Diabetic Nephropathy Prevention, 2017)
Background: Gram-negative bacteria are associated with an increase in rates of antibacterial resistance. In most low- and middle-income countries such as Iran, there is no continuous surveillance system for antibiotic resistance. Objective: The purpose of this survey was to determine the pattern of antimicrobial sensitivity of gram-negative bacteria within 3 consecutive years at a nephrology ward of Nemazee hospital in Shiraz. Materials and Methods: During a 3-year period from 2013 to 2015 at the adult nephrology ward, bacteriological data of all biological samples of hospitalized patients in favor of gram-negative microorganisms were analyzed retrospectively. Antimicrobial susceptibility was performed by the Kirby-Bauer disc diffusion method. Results: The most common gram negative bacterium isolated from biological samples was Escherichia coli (43.9%). The highest (86.3%-94.1%) antibacterial resistance rate was associated with Acinetobacter spp. The most frequent resistance was seen with cephalosporins. In contrast to ceftriaxone, ciprofloxacin, and trimethoprim/sulfamethoxazole, nitrofurantoin and aminoglycosides remained their acceptable activity against E. coli. At least three-fourths (75%) of Acinetobacter spp. isolates was resistant to either aminoglycosides or imipenem. All (100%) isolated Acinetobacter spp. and Pseudomonas aeruginosa species were susceptible to colistin. The rate of Acinetobacter spp. and P. aeruginosa resistant to three or more drugs was 81.7% and 74.6%, respectively. Conclusions: The resistant rate of gram negative pathogens to different tested antibacterial agents was considerably high and has increased during the recent three years in our center.